Physical Model and Calculation of Face Packing Seals - Shevchenko, Serhii S. (Інститут енергетичних машин і систем ім. А. М. Підгорного Національної академії наук України, 2021)
Increasing the reliability and service life of dynamic-pump shaft seals is the most important requirement for their creation. The most common type of seals is still traditional stuffing box seals, which are controlled leakage assemblies that are periodically restored during operation. A radical change in the design of standard stuffing box seals is the transition to face packing seals with a constant pressure against the packing. It is shown that face packing seals can successfully combine the advantages of mechanical face seals and the simplicity and relatively low cost of traditional stuffing box seals. Mechanical face seals, in which one of the packing rings is replaced by a stuffing box packing, have advantages that significantly expand the application of traditional stuffing box seals. A scheme and a physical model of the face packing seal operation are described. During the operation of the seal, the packing is pushed away from the mating metal surface by the pressure of the medium. In this case, a confusor gap is formed, the length of which is proportional to the ratio of the sealed pressure to the pre-compression pressure of the packing. The calculation of the distribution of the hydrostatic pressure and gap along the radius of the face joint of the seal is presented. The irregularity of the contact pressure along the radius, caused by the pressing out of the packing by the sealed inlet pressure, causes premature wear of the overloaded areas of contact surfaces. Expressions are proposed for estimating friction power losses in face packing seals. It is shown that these losses are significantly lower in comparison with the power losses in traditional stuffing box seals. Assessment of the thermal state of face packing seals has been carried out. An expression has been obtained for determining the flow rate that provides the average contact-surface temperature not exceeding the permissible value. Our studies have shown that the load factor of face packing seals, in contrast to mechanical face seals, must be close to unity. The obtained dependencies make it possible to calculate face packing seals at their design stage.